Building Hoopes vision - Calkins, Tim (SAGE Knowledge. Cases., 2018)
Dr. Phillip Hoopes, a LASIK surgeon, is considering how to respond to discounting by his competitors. He had built a high-end practice with costly advanced technology, but discounters had recently entered the market and other high-end practices in the area were starting to offer deep promotions in an effort to compete.